Alleged Deviations from Religious Teachings at the Al Zaytun Islamic Boarding School in Online News Portals: Critical Discourse Analysis of Teun A. van Dijk's Model - Haryanti, Putri; Rakhmawati, Ani (Universitas Muhammadiyah Malang, 2024)
Lately, the allegations of deviations from religious teachings that occurred at the Al Zaytun Indramayu Islamic Boarding School have become a hot topic of discussion. The fact that the leadership of the Islamic boarding school deviated from religious teachings raises concerns for the Indonesian people as a whole. Islamic boarding schools should be the center of religious civilization. The purpose of this study is to analyze text structure, social cognition and social context in the news Tribunnews.com, Sindonews.com, and Liputan6.com regarding alleged deviations from religious teachings that happened at Al Zaytun Islamic Boarding School. The source of research data comes from the online news portals about alleged deviations from religious teachings that occurred at the Al Zaytun Islamic Boarding School. This research is a type of qualitative research that uses data collection methods through documentation, observation, observation, and direct recording. Data analysis methods used include reduction, presentation, and verification. The findings from the research show that three news stories have the same theme and topic, namely informing about alleged deviations from religious teachings that took place at Al Zaytun Islamic Boarding School. The three stories have been analyzed using the discourse analysis model by Teun A. van Dijk. The results of critical discourse analysis conclude that the news presented included in the criteria for critical analysis according to Teun A. van Dijk's model, includes (1) text structure, (2) social cognition, and (3) social context. This research has implications for the implied message, which expects readers to be more careful in choosing news portals. Apart from that, it is also appealed to the general public to be aware of any deviant actions that might occur even in an environment that is considered to be religious.